THE ROLE OF MEDIA IN CREATING AWARENESS ON CHILD SEXUAL ABUSE AMONG SCHOOL STUDENTS - Sharma, Archana (Journal of Education Culture and Society, 2020)
Aim. This study aims to analyse the role of media in creating awareness on child sexual abuse and Good Touch Bad Touch among children. The research also aims to study the students’ awareness level of Child Sexual Abuse which includes the Good Touch Bad Touch. Method. The survey research method was used to collect data, through a well-structured questionnaire from 100 respondents of a school from a city of Punjab, constituting 20 respondents from each class, selected through convenient sampling.Result. The findings reveal that the media failed to create awareness on child sexual abuse among children. 90% of the respondents were not aware of any child sexual abuse or child helpline number.Conclusion. Even though, some initiatives were taken by various media tools to raise the child safety issue in the society, but those are not enough. There is a need to develop and run more specific programs regularly to raise awareness throughout society on child sexual abuse.